Understanding digital drug markets through the geography of postal drug deliveries in Scotland - Matthews, Ben (European journal of criminology, 2023)
An increase in the use of postal services to deliver drugs purchased online raises concerns about widening access to drugs markets, especially in remote and rural areas that were previously protected by geographical boundaries. Yet little is known about the geographical patterning of drugs delivered through the post. Using a novel law enforcement dataset containing details of illegal drug packages intercepted by UK Border Force en route to Scotland, we examine the geographical destination of drugs purchased online and explore the area-based characteristics associated with higher rates of delivery. This article provides previously unavailable insights into the spatial patterning of digital drugs markets at sub-national level. We use descriptive statistics, Bayesian hierarchical regression models, and spatial autocorrelation to describe the relationship between area-based characteristics and expected rate of illegal drug consignments identified across Scotland. The majority of intercepted drug packages were destined for urban centres, but there was a higher than expected delivery rate to some of Scotland?s remote and rural locations. Increased rates of drug delivery within Scottish neighbourhoods was independently associated with higher levels of crime and deprivation, with Internet connectivity and with access to services, but not with higher rates of drug-related hospitalization. Analysis of spatial clustering showed that drug delivery to the most remote and rural locations was still associated with good access to services because the packages were typically delivered to addresses in larger settlements within remote locations. Overall, postal drugs delivery reflects both relatively high use in more urban, more deprived areas but also seems to open up more remote regions to drug markets, albeit with usage concentrated in larger settlements within otherwise remote areas.